*The significance of p-ANCA in differing chronic amebic colitis from ulcerative colitis complicated with amebic colitis - Serap ARSLAN; Yusuf AKCAN; Ayşin BAKKALOĞLU; Serdar TUNCER; Emin KANSU; Serhat ÜNAL; Sibel ERGÜVEN; Fikri CANORUÇ; Bedri UZUNALİMOĞLU and Burhan KAYHAN 0 (Turkish Journal of Gastroenterology, 2019)
-